2011
DOI: 10.1016/j.sab.2011.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Iron speciation in human cancer cells by K-edge total reflection X-ray fluorescence–X-ray absorption near edge structure analysis

Abstract: X-ray absorption near edge structure (XANES) analysis in combination with synchrotron radiation induced total reflection X-ray fluorescence (SR-TXRF) acquisition was used to determine the oxidation state of Fe in human cancer cells and simultaneously their elemental composition by applying a simple sample preparation procedure consisting of pipetting the cell suspension onto the quartz reflectors. XANES spectra of several inorganic and organic iron compounds were recorded and compared to that of different cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…For the TXRF-XANES measurements, HT-29 cells were treated for 3 h separately with 20 μM Rh 2 (OAc) 3 (O-Phe-Z) 1 and Rh 2 (O-Phe-Z) 4 each. Then, treated cells were further processed according to our previously published method [37]. Briefly, cells were harvested by trypsin, washed twice with an isotonic NaCl solution and centrifuged at 7000 rpm.…”
Section: Cell Culture and Sample Preparation For Txrf And Txrf-xanesmentioning
confidence: 99%
See 1 more Smart Citation
“…For the TXRF-XANES measurements, HT-29 cells were treated for 3 h separately with 20 μM Rh 2 (OAc) 3 (O-Phe-Z) 1 and Rh 2 (O-Phe-Z) 4 each. Then, treated cells were further processed according to our previously published method [37]. Briefly, cells were harvested by trypsin, washed twice with an isotonic NaCl solution and centrifuged at 7000 rpm.…”
Section: Cell Culture and Sample Preparation For Txrf And Txrf-xanesmentioning
confidence: 99%
“…The aims of the present study were: i) investigation of the cellular Rh content originating from dirhodium(II) complexes of D-and L-isomers of phenylalanine derivatives and chelate and bridging type of geometry, respectively, as potential anticancer drugs; ii) determination of in vitro cytotoxicity and cytostatic activities of these compounds; iii) characterization of the chemical environment of these Rh containing complexes in HT-29 cells. In order to achieve these goals, totalreflection X-ray fluorescence (TXRF) spectrometry [35] complemented with the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium (MTT) assay and X-ray absorption near edge structure (XANES) analysis were performed for quantitative determination and elemental speciation of cellular samples [36,37], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In saliva the most significant differences were found for the elements Ca and K, whereas for gingival crevice fluid the most significant difference between both groups was found for Cl. Polgari et al 121 applied the recently developed combination of SR-TXRF with XANES for biochemical studies. This powerful instrumental configuration combined with simple sample preparation (by pipetting and drying the cell suspension on the quartz reflectors) enabled Fe speciation in human cancer cells by K shell XANES in total reflection geometry.…”
Section: New Applications and Developments In Instrumentationmentioning
confidence: 99%
“…A novel study was reported by Polgari et al 143 in which Fe speciation in cancer cells was investigated using SR-TXRF and XANES. Cell suspensions were pipetted onto the quartz reflectors for spectral measurements and the collected spectra compared with spectra from analysis of pure organic and inorganic Fe compounds.…”
Section: Ironmentioning
confidence: 99%